Accounts of Biological Functions for Accumulation of Radioisotopes in Fishes - KATSURA Hidemitsu (Accounts of Biological Functions for Accumulation of Radioisotopes in Fishes, 2021)
The Tokyo Electric Power Company Fukushima Dai-ichi nuclear power plant in Fukushima-Ken (Prefecture), Japan, was destroyed in March 2011 due to a massive earthquake (magnitude 9) centred offshore to the northeast of Honshu Island and the subsequent historic tsunami on 11 March 2011. Due to nuclear meltdown, damage to the buildings housing the reactors by hydrogen explosions, and the contamination of cooling water from the reactor cores, huge quantities of radioisotopes were emitted to the atmosphere and to the adjacent seawater. Fishing is currently restricted off the coast of Fukushima-Ken because intermittent surveys have found that the majority of fishery products still contain radioisotope levels exceeding the Japanese Standard Value. The Tokyo University of Marine Science and Technology has measured radioisotope levels in fishery species off Iwaki-Shi(Iwaki City), Fukushima-Ken (located south of the former nuclear power plant); these data could be used to understand the relationship between the accumulation of specific nuclides (radioisotopes) and certain species of fish, as described in the following chapters: Chapter 1 "Accumulation of a Specific Nuclide by Female Common Skete (Feminam Okamejei kenojei spp.)" Chapter 2 "Total Quantity of Caesium Radioisotopes in Fish in the Fukushima-Ken Exclusive Economic Zone, Japan, in November 2012" Chapter 3 "Some Fish Species in Offshore Fukushima, Japan have the Ability to Accumulate a Specific Nuclide (Radioisotope)" Chapter 4 "Possible Atomic Fuel Production through Accumulation of Specific Radioisotopes by Fish in Offshore Fukushima, Japan".